The prospects for development of the conflict of laws provisions to regulate relations with involvement of the Republic of Belarus - Yevmenchikovа Оlga A. (Journal of the Belarusian State University. Law, 2020)
The article is devoted to the research of the conflict of laws provisions to regulate relations which the Republic of Belarus is involved in. Accordingly to the analysis of the legislation of the Republic of Belarus author highlights law-making factors that define the law applicable to the contracts with State involvement. The author suggests the recommendations for further development of the legislation of the Republic of Belarus.